Anthropic impact on soil heavy metal contamination in riparian ecosystems of northern Algeria. (February 2023) - Napoletano, Pasquale; Guezgouz, Noureddine; Di Iorio, Erika; Colombo, Claudio; Guerriero, Giulia; De Marco, Anna
Abstract: The aim of this research was to highlight the impact of urbanization and agriculture on soil quality, mainly by focusing on heavy metal accumulation (Cd, Cu, Fe, Mn, Ni, Pb and Zn) in the fragile riparian ecosystems of the Medjerda river (Souk-Ahras, Algeria). This study was performed in three cultivated soils (0–10, 10–20, 20–60 cm depth) along an increasing gradient of anthropogenic pressure in non-urban (NU), peri-urban (PU) and urban areas (U). Geo-accumulation index (Igeo), Enrichment factor (EF), Pollution load index (PLI) and Potential ecological risk index (RI) were calculated, as well as the potential non-carcinogenic risk for humans (HI). Additionally, to corroborate the role of Bufo spinosus D. as biosentinel, a skin biopsy was performed to quantify the concentration of heavy metals in both terrestrial and aquatic ecosystems. The results showed that when compared to NU, U and PU areas were richer in heavy metals. In particular, Igeo-Cd displayed strongly contaminated soil in U (>3), EF showed high enrichment of heavy metals (>2) for all the soils except for Ni, PLI presented no contamination for all (<1) while RI was significantly higher in U (>300), denoting a strong impact of heavy metals on soil quality. However, HI was below 1 for all the studied areas, although the highest values were related to U and PU. The skin biopsy showed the highest values for Cu, Fe and Pb in PU (0.328, 0.713 and 0.524 mg kg −1, respectively) similarly to trends observed in the soil of that area. This study shed light on the rising pollution of heavy metals due to urbanization and agricultural input in these fragile ecosystems where Bufo spinosus D. plays the role of potential bio-indicator for environmental pollution. Graphical abstract: Image 1 Highlights: Urbanization and agriculture exert a combined effect on the soil heavy metal content. Soils showed a high Cd and Zn content related to both fertilizer use and urban origin. In the peri-urban area the content of Cu, Fe and Pb was higher in both soil and skin. The toad skin showed a particular sensitivity for Cu, Fe and Pb contamination. The ecological risk index reported high risk in urban, non-urban and peri-urban areas.